2017
DOI: 10.1186/s12906-017-1706-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic effects of oridonin

Abstract: BackgroundOridonin, the major terpene found in Rabdosia rubescens (Henmsl.) Hara, is widely used as a dietary supplement and therapeutic drug. Oridonin has been proven to possess good anti-tumour activity, but little is known about its effect on angiogenesis. The aim of this study was to investigate the antiangiogenic effects of oridonin in vivo and in vitro and prove that oridonin anti-tumour activity is based on suppressing angiogenesis.MethodsIn vitro, the antiangiogenesis effect was studied by proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…Oridonin was also found to block the angiogenesis of zebrafish by decreasing the mRNA expression of vascular endothelial growth factor A (VEGFA), vascular endothelial growth factor receptor 2 (VEGFR2) and VEGFR3, while reducing the expression of metastatic proteins claudin-1, -4, and -7. Antimetastatic activity of oridonin was further confirmed in a xenograft zebrafish model tested at a dose of 8 mg/kg that showed significant effect (p < 0.01) in comparison to the vehicle control group [24]. Gao et al (2016) reported that oridonin induced apoptosis by downmodulating the expression level of B-cell lymphoma 2 (BCL-2), but upmodulating the expression of BAX, thus reducing the BCL-2/BAX ratio in human gastric cancer SGC-7901 cells.…”
Section: Oridoninmentioning
confidence: 87%
See 1 more Smart Citation
“…Oridonin was also found to block the angiogenesis of zebrafish by decreasing the mRNA expression of vascular endothelial growth factor A (VEGFA), vascular endothelial growth factor receptor 2 (VEGFR2) and VEGFR3, while reducing the expression of metastatic proteins claudin-1, -4, and -7. Antimetastatic activity of oridonin was further confirmed in a xenograft zebrafish model tested at a dose of 8 mg/kg that showed significant effect (p < 0.01) in comparison to the vehicle control group [24]. Gao et al (2016) reported that oridonin induced apoptosis by downmodulating the expression level of B-cell lymphoma 2 (BCL-2), but upmodulating the expression of BAX, thus reducing the BCL-2/BAX ratio in human gastric cancer SGC-7901 cells.…”
Section: Oridoninmentioning
confidence: 87%
“…A wide variety of sources have reported the anticancer mechanism of oridonin in multiple cancer cell lines [17,24,27,[29][30][31][32]. According to the study of Yao et al (2017) oridonin induced autophagy by decreasing the protein levels of glucose transporter 1 (GLUT1) and monocarboxylate transporter 1 (MCT1) in SW480 human colorectal cancer cells, in the BALB/c xenograft model.…”
Section: Oridoninmentioning
confidence: 99%
“…As an orally available drug, oridonin is demonstrated to have anti-cancer activities in multiple cancers over the past decades, including leukemia, lymphoma, osteosarcoma, myeloma, uveal melanoma, neuroblastoma, hepatocellular, laryngeal, esophageal, and oral squamous cell carcinoma, lung, colorectal, breast, gastric, pancreatic, and prostatic cancers [543][544][545][546][547][548][549][550][551][552][553][554][555][556][557][558]. The anti-cancer effects of oridonin are shown in many aspects, including the induction of cell apoptosis, autophagy, cell cycle arrest, and the suppression of angiogenesis, cell migration, invasion and adhesion [554,[559][560][561][562][563][564].…”
Section: Oridoninmentioning
confidence: 99%
“…The anti-cancer effects of oridonin are also shown to be through suppressing angiogenesis and metastasis, which are the primary causes of tumor growth and metastasis. It can inhibit cell migration and invasion, and tube formation in human breast cancer 4T1 and MDA-MB-231, human and murine melanoma A375 and B16F10, osteosarcoma MG63 and 143B, and HUVECs, as well as tumor metastasis in HepG2 xenograft zebrafish and mice, 4T1 xenograft mice, and 143B xenograft mice [554,[562][563][564]573].…”
Section: Oridoninmentioning
confidence: 99%
“…Oridonin, which is purified from the Chinese herb Rabdosia rubescens , is an active diterpenoid compound. In recent years, various studies have demonstrated that oridonin has multiple biological activities, including anti‐angiogenic and anti‐proliferative effects, and displays a potent apoptotic effect in many types of cancer cell lines . Previous studies also have shown that oridonin induces apoptosis in several cancer cell lines by regulating mitochondrial proteins and phosphoinositide 3‐kinase (PI3K)/Akt and mitogen‐activated protein kinases (MAPKs) signaling pathways .…”
mentioning
confidence: 99%